KAMPANYE STRATEGIS MELAWAN RADIKALISME: MERANCANG MODEL PENDIDIKAN MULTIKULTURAL | A STRATEGIC CAMPAIGN AGAINST RADICALISM: A PLANNING MODEL FOR MULTICULTURAL EDUCATION - Yosef Keladu Koten (Jurnal Ledalero, 2018)
Abstract: Radicalism seriously threatens modern pluralistic communities. In recent times, many national states have put in place strategic plans to fight against radicalism, or to lessen the impact of radical ideas or behaviour. This is known as the process of de-radicalisation. This isn’t an easy process there are many reasons behind the growth of radicalism. One of these is the simple acceptance of differences without trying to understand those differences and the similarities of the people of a country. This can be signified by, and caused by a process of uniformity, which can be seen in the system of education. With this in mind, this article proposes a strategic, effective campaign against radicalism, beginning with a model of multicultural education. Multicultural education promotes the principle of inclusiveness, diversity, democracy and critical thinking which is appropriate for a pluralistic country which enables the education of people to live in a multicultural community. Keywords: Radicalism, inability to think, diversity, ideology, multiculturalism, multicultural education. Abstrak: Radikalisme menyebarkan ancaman serius terhadap komunitas pluralistis modern. Selama beberapa dekade terakhir, banyak negara di dunia menetapkan rencana-rencana strategis untuk berperang melawan radikalisme atau untuk mengurangi ide-ide atau perilaku radikal. Yang terakhir ini disebut dengan proses de-radikalisasi. Proses seperti ini tidak gampang karena banyaknya alasan di balik munculnya radikalisme dan salah satunya ialah karena adanya perilaku menerima begitu saja perbedaan tanpa ada upaya untuk memahami perbedaan dan kesamaan semua anggota dari sebuah negara. Hal ini ditengarai, disebabkan salah satunya oleh proses penyeragaman, termasuk dalam sistem pendidikan. Oleh karena itu, artikel ini menganjurkan sebuah kampanye strategis yang efektik untuk melawan radikalisme yaitu dimulai dengan merancang sebuah model pendidikan multikultural. Pendidikan multikultural mempromosikan prinsip inklusi, diversitas, demokrasi, dan pemikiran kritis yang cocok untuk sebuah negara plural yang memampukan peserta didik untuk hidup dalam sebuah komunitas multikultural. Kata-kata Kunci: radikalisme, ketidakmampuan berpikir, kebhinekaan, ideologi, multikulturalisme, pendidikan multikultural